Pain during the first year after scoliosis surgery in adolescents, an exploratory, prospective cohort study - de Leeuw, Thomas G.; Boerlage, Anneke A.; van West, Hanneke M.; Renkens, Jeroen J. M.; van Rosmalen, Joost; Staals, Lonneke M. E.; Weber, Frank; Tibboel, Dick; de Wildt, Saskia N. (Frontiers in Pediatrics, 2024)
Objective: Approximately 50% of adolescents who have undergone scoliosis surgery still experience severe pain one year postoperatively. We explored the postoperative pain trajectory and the potential value of preoperative Thermal Quantitative Sensory Testing (T-QST) as predictor of chronic postsurgical pain after scoliosis surgery. Design: Single-center prospective cohort study in adolescents undergoing scoliosis surgery. Outcomes: Prevalence of chronic postsurgical pain (CPSP) one year after scoliosis surgery and postsurgical pain course during this year. The need for rescue medication and the relationship between pre-operative T-QST, acute pain and CPSP. Results: Thirty-nine patients (mean age 13.9 years; SD 1.9 years) completed the study. One year postoperatively, ten patients (26%) self-reported pain (numeric rating scale (NRS) score ≥ 4)) when moving and two (5%) when in rest. Four of these patients (10.3%) experienced neuropathic pain. The pre-operative cold pain threshold was lower (p=0.002) in patients with CPSP at 12 months. Preoperative cold and heat pain thresholds were correlated with the number of moderate or severe pain reports (NRS ≥ 4) in the first week postoperatively (r -.426; p = 0.009 and r .392; p = 0.016, respectively). Conclusions: One year after scoliosis surgery, a significant part of patients (26%) still reported pain, some with neuropathic characteristics. Better diagnosis and treatment is needed; our study suggests that T-QST could be further explored to better understand and treat children with this negative outcome.